A large-scale field test on sand compaction piles including three-dimensional numerical analysis. (21st May 2020) - Hongtao, He; Jianyu, Li; Yougao, Lin
This paper presents a large-scale field test study performed on soft ground improved by a set of 216 sand compaction piles in a mesh of 12 × 18 columns, with plan dimensions of 32.2 m × 21.4 m loaded with anchor piles loading system. The objective of this study was to verify the performance of foundation improvements with sand compaction piles for the future immersed tunnel. The field test was also useful to calibrate a numerical model for predicting the behaviour of the permanent immersed tunnel on sand compaction piles composite foundation. Three-dimensional finite element analysis was firstly carried out and the results of field measurements and numerical calculations were compared. In general, the numerical calculations of vertical displacements reproduced the field measurements with satisfactory accuracy. Calculations of effective stress and stress concentration ratio had less satisfactory agreement, and some reasons are provided for this.